THE COMMUNICATION PATTERN IN THE COOPERATION RELATIONSHIP BETWEEN ANTV TELEVISION STATION AND KOMANDO PRODUCTION HOUSE AT PESBUKERS PROGRAM - Muslim . (JHSS (JOURNAL OF HUMANITIES AND SOCIAL STUDIES), 2020)
The purpose of this research is to know the communication pattern in the cooperation relationship between ANTV television station and KOmando production house at Pesbukers program and to know the production process done by cooperation between ANTV television station with KOmando production house (pra-production, production, until post-production) on the Pesbukers program, as well as to find out what problems will occur in the cooperation relationship between ANTV television station and KOmando production house on Pesbukers program. This research uses a qualitative research approach, because this research requires field observation and also researchers conducted interviews with the sources related to this research to obtain valid data. This research uses relationship theory, known by the name Palo Alto Group according to Stephen W. Littejohn [4]. ANTV joined with KOmando production so that cooperate and form a relationship as "Group" or group in Pesbukers program, that is a number of people exist between relations each other and the interconnection is a structure. Sources of data used in this study consist of primary and secondary. Primary data include conducting in-depth interviews on Key Informants, such as Producer in ANTV at Pesbukers and Informant program, such as Producer at KOmando Production, and Screenwriter at KOmando Production on Pesbukers program. While secondary data include documents related to the program event as well as various libraries or expert opinions sourced from books or from links. In the triangulation stage of the data held interviews with observers, he has the experience of being a Dubber, Screenwriter, and Director in a Production House.